EVALUASI MANAJEMEN SISTEM INFORMASI DAN TEKNOLOGI INFORMASI PELABUHAN - Budi Sitorus; Tulus Irpan Harsono Sitorus; Prasadja Ricardianto (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2016)
The purpose of the research is to identify the problem in the port management information system, analyze what needs to be managed in the port management information systems, provide recommendations on the management of information systems management. The research method uses a qualitative analysis approach, in which the port management is still unsatisfactory, therefore, to manage port services requires technology application-based management information system the one that is currently being developed is Inaportnet, in the early stages of this technology application used for the port is already cultivated. The expected result is that the application of information technology-based systems are expected to increase the harbor management performance and the government is expected to direct, supervise and enforce the stakeholders in the port who violate the rules.